Cavernous hemangioma of the mitral valve – a rare heart tumor. А clinical case - R.M. Vitovsky; O.A. Pishchurin; M.M. Serdyuk; V.V. Isaienko; V.F. Onishchenko (Кардіохірургія та інтервенційна кардіологія)
The article presents a clinical case of a rare benign heart neoplasm – a cavernous mitral valve hemangioma. Infiltrative growth of the tumor led to deformation of the valve with the development of mitral insufficiency and its replacement with a mechanical prosthesis.